2010 International Conference on Electronics and Information Engineering 2010
DOI: 10.1109/iceie.2010.5559741
|View full text |Cite
|
Sign up to set email alerts
|

Design of S-boxes based on neural networks*

Abstract: In this paper, we present a framework for the design of S-boxes used in ciphers based on neural networks. It can yield S-boxes with different input and output length. The designed S-boxes satisfy the desired cryptographic properties of non-linearity, completeness, strict avalanche, and output bits independence criteria. We propose a four layer topology, where the number of neurons, located at the input layer, is two times the number of input bits of the designed Sbox and also, the number of neurons, located at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Another study discussed the theoretical aspects of applying NNs to encrypted data [80]. Various experimental studies showed how an artificial agent can learn a secure encryption method and the use of RNN and CNN based methods for S-box and cipher design as well as their classification [82] [83] [84] [85] [86]. Further, cryptonets, a set of NNs with DL was proposed to allow the user to send the encrypted data to the cloud and the models were trained to predict risks without decrypting the data with various experiments to enhance their performance [87] [88].…”
Section: DL For Cryptographymentioning
confidence: 99%
“…Another study discussed the theoretical aspects of applying NNs to encrypted data [80]. Various experimental studies showed how an artificial agent can learn a secure encryption method and the use of RNN and CNN based methods for S-box and cipher design as well as their classification [82] [83] [84] [85] [86]. Further, cryptonets, a set of NNs with DL was proposed to allow the user to send the encrypted data to the cloud and the models were trained to predict risks without decrypting the data with various experiments to enhance their performance [87] [88].…”
Section: DL For Cryptographymentioning
confidence: 99%
“…The detailed experimental analysis on RNN based methods for cipher design was done by [142]. In [143] showed detailed experimental analysis of NNs on the design of S-boxes used in ciphers. Cryptographic Primitive classification based on CNN was done by [144].…”
Section: Deep Learning For Cryptographymentioning
confidence: 99%
“…Due to their importance, S-boxes are chosen and designed to be resistant to cryptanalysis, in literature several proposals with different characteristics are found, some of them based on neural networks, like the framework for the design of S-boxes used in ciphers based on neural networks by Noughabi (Noughabi & Sadeghiyan, 2010) and "a new scheme for implementing s-box based on neural network" by X. Zhang (Zhang, Chen, Chen, & Cao, 2015), others that optimize existing boxes such as the high speed implementation of S. Oukili for the AES Sbox (Oukili, Bri & Kumar, 2016) and low-area S-box implementation of Thomson (Thomson, Siva, & Priya, 2014); even new proposals such as the evolutionary design of S-Box of M. Yang (Yang, Wang, Meng & Han, 2011) and the based on chaotics maps of C. I. Rı̂ncu (Rı̂ncu & Iana, 2014). This article presents a substitution of the S-box for another module that calculates the AES S-box outputs with the use of a neural network and the multiplicative inverse on Galois field 2 8 (GF (2 8 )) of the input value to transform, or S-box input value.…”
Section: Figure 1 Graphic Representation Of the Use Of An S-boxmentioning
confidence: 99%